A Note on Imperfect Information and Optimal Pollution Control - Repullo, Rafael (Review of Economic Studies, 1982)
Journal Article A Note on Imperfect Information and Optimal Pollution Control Get access Rafael Repullo Rafael Repullo London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 49, Issue 3, July 1982, Pages 483–484, https://doi.org/10.2307/2297372 Published: 01 July 1982